2009
DOI: 10.1002/art.24259
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of articular cartilage frictional properties by transforming growth factor β, interleukin‐1β, and oncostatin M

Abstract: Objective. To evaluate the functional effects of transforming growth factor ␤1 (TGF␤1), interleukin-1␤ (IL-1␤), and oncostatin M (OSM) on the frictional properties of articular cartilage and to determine the role of cytokine-mediated changes in cartilage frictional properties by extracting and redepositing lubricin on the surface of cartilage explants.Methods. Neonatal bovine cartilage explants were cultured in the presence or absence of 10 ng/ml of TGF␤1, IL-1␤, or OSM over 48 hours. Boundary lubrication test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
5
12
0
Order By: Relevance
“…The significant decrease in COF in MSCs group of the present study was consistent with the significant COF decrease in equine synovial fluid soaked, MSCs alginate construct by 10% after 4 weeks of MSCs culture and by 20% after 6 weeks of MSCS culture [47]. Moreover, the decrease in COF might be as a consequence of slight decrease in IL-1b and TNF-a in MSCs group [48]. The objectives of cartilage repair are support and load distribution as mechanical properties and low friction provided by proper lubrication and normal cartilage structure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The significant decrease in COF in MSCs group of the present study was consistent with the significant COF decrease in equine synovial fluid soaked, MSCs alginate construct by 10% after 4 weeks of MSCs culture and by 20% after 6 weeks of MSCS culture [47]. Moreover, the decrease in COF might be as a consequence of slight decrease in IL-1b and TNF-a in MSCs group [48]. The objectives of cartilage repair are support and load distribution as mechanical properties and low friction provided by proper lubrication and normal cartilage structure.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the outcome measures including WOMAC questionnaire are subjective [44][45][46]. Moreover, the decrease in COF might be as a consequence of slight decrease in IL-1b and TNF-a in MSCs group [48]. The significant decrease in COF in MSCs group of the present study was consistent with the significant COF decrease in equine synovial fluid soaked, MSCs alginate construct by 10% after 4 weeks of MSCs culture and by 20% after 6 weeks of MSCS culture [47].…”
Section: Discussionsupporting
confidence: 84%
“…25,29,52 Briefly, cylindrical full thickness osteochondral samples (n ¼ 144) were harvested with a biopsy punch using aseptic techniques from the patellofemoral groove of 11 stifle joints of 1-to 3-day-old calves. Cartilage was removed from the bone with a scalpel resulting in 6 mm diameter and $2 mm thick cartilage samples with the articular surface intact.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Cartilage adjacent to the cylindrical sample areas was also harvested in a similar manner for histological analysis of the native tissue. Cartilage samples were placed in tissue culture using standard culture media 15,52 and friction tested within 5 days after harvest. Equine synovial fluid (ESF) from the stifle joints of three skeletally mature horses (ages 3-5 years) (College of Veterinary Medicine, Cornell University, Ithaca, NY) was aspirated, visually inspected to ensure it was free of blood and contaminants, pooled, and stored at À208C for no more than 3 months.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Additionally, a number of cytokines and growth factors are involved in the regulation of lubricin expression in the ACL-injured knee. As an anabolic factor, TGF-β1 upregulates the synthesis and surface localization of lubricin (67,68), whereas IL-1 or TNF downregulate the production of lubricin (69,70). In an animal model of posttraumatic arthritis, it has been demonstrated that blocking TNF increases lubricin production on the surface of articular cartilage (71).…”
Section: Biomarkers Of Cartilage Degenerationmentioning
confidence: 98%